Epidemiological survey of Toxoplasma gondii and Neospora caninum infections in dairy goats in Central-Southern Taiwan - CHIANG, Shou-Heng; HUANG, Han Hsiang; CHOU, Chi-Chung; CHU, Chi-Shih; SHIH, Wen-Ling; LAI, Jyh-Mirn; LIN, Heng-Ching; YANG, Wei-Cheng; LEE, Hsu-Hsun; TSAI, Yi-Lun; SU, Yao-Chi (Journal of Veterinary Medical Science, 2020)
Toxoplasma gondii and Neospora caninum are intracellular protozoan parasites that cause reproductive disorders in ruminants and humans. Information on the risk factors of T. gondii and N. caninum infections in goats is very limited in Taiwan. The aim of the study was to investigate the epidemiology and identify the risk factors of these two infections in goats. A total of 630 caprine sera were collected from 42 dairy goat farms and the owners were interviewed by a structured questionnaire. The apparent seroprevalences of T. gondii in farm- and individual- levels were respectively 88.1% and 32.22%, while those of N. caninum were 19.05% and 2.54%, respectively. Toxoplasma gondii B1 gene was identified in 7 feed samples and 8 from the water samples whereas N. caninum was not found. Wooden flooring was the main risk factor for T. gondii infection while the frequency of visits by staff to other farms and the breed of goat were risk factors for N. caninum. The improvement of flooring materials or thorough cleaning, periodic disinfection and maintenance of dryness on the floor are highly recommended for the prevention of T. gondii infection in farmed goats. In addition, unnecessary visits to other farms should be limited to prevent the spread of N. caninum. These factors should be highlighted for the prevention of T. gondii and N. caninum in goats, particularly when raised in intensive housing system with flooring on height.